ELECTORAL POLITICS AND CONFRONTING THE CHALLENGE OF BASQUE AND MORO NATIONALISM - Encarnacion Tadem, Teresa S. (Social Science Diliman: A Philippine Journal of Society and Change, 2011)
This article explores the similarities and differences concerning the extent to which electoral politics addresses the concerns of Basque and Moro nationalism.  These demands mainly focus on the factors that have brought about their political, cultural and, for the Moros, also economic marginalization.  In terms of similarities, electoral politics in the form of plebiscites and referendums are used to gauge the sentiments of the Basques and the Moros with regards to approving a national constitution with provisions affecting them as well as the establishment of an autonomous region for the Moros and the strengthening of a federal form of government in the case of the Basques.  Elections are also used to choose their leaders at the local, provincial, regional and national levels.  As for the differences, among the major ones are the following:   One is that electoral politics in the Basque region mirrors the class divide in society and reflects the interests of the constituencies.  This is not the case in Muslim Mindanao whereby patronage politics rules and electoral results are generally dictated by the Muslim elites who have close ties with the national elites. And secondly, the ideological bias of the elected leader and his political power in Spain has a direct impact on Basque nationalism. In the case of the Philippines, it is the personality of the elected leader that determines whether peace negotiations will be pursued or not.  But this does not impact on national or local electoral politics as in the case of Spain.
Keywords: Electoral politics, nationalism, Basque, Moro, separatism, marginalization